The little engine that could - Piper, Watty, pseud; Hauman, George; Hauman, Doris (New York : Platt & Munk, 1976)
A little blue engine comes to the rescue of a train that is loaded with toys, dolls, and good things to eat, but cannot get over the mountains to deliver the cargo to waiting children.
Wilson's Children
3.9
K-3
Keywords: Locomotives -- Fiction; Toys -- Fiction; Motivation (Psychology) -- Fiction; Trains -- Fiction; Railroads -- Fiction; Motivation (Psychology) -- Fiction